2022
DOI: 10.1093/humrep/deac107.414
|View full text |Cite
|
Sign up to set email alerts
|

P-439 Human Platelet Lysate improve the growth and survival of isolated human pre-antral follicles in vitro

Abstract: Study question Can human Platelet Lysate (hPL) and umbilical cord plasma (UCP) be used as alternative serum sources in the culture of isolated human pre-antral follicles? Summary answer hPL significantly increased the growth and survival of human follicles cultured for 8 days compared to fetal bovine serum (FBS) and human serum albumin (HSA). What is known already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…This difference is most likely explained by differences in media composition: Xu and co-workers used 3 mg/mL bovine serum albumin (BSA) and 1 mg/mL fetuin during the culture, while we employed 5% foetal bovine serum (FBS). Evidence in mice and humans has demonstrated that various serum-derived products impact preantral follicle growth differently in vitro [32][33][34]. In particular, FBS contains more than a thousand components, including proteins, hormones, growth factors, enzymes, and other undefined constituents, which generate potential batchto-batch variations, making comparing results from different studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is most likely explained by differences in media composition: Xu and co-workers used 3 mg/mL bovine serum albumin (BSA) and 1 mg/mL fetuin during the culture, while we employed 5% foetal bovine serum (FBS). Evidence in mice and humans has demonstrated that various serum-derived products impact preantral follicle growth differently in vitro [32][33][34]. In particular, FBS contains more than a thousand components, including proteins, hormones, growth factors, enzymes, and other undefined constituents, which generate potential batchto-batch variations, making comparing results from different studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, culture media supplemented with PRP was shown to support the growth and survival of early preantral follicles significantly better than media without PRP [61]. In comparison to other growth supplements routinely used in culture media, such as human serum albumin and fetal bovine serum, human platelet lysate (hPL), a derivative of PRP, has demonstrated improvement in follicular growth and survival of isolated primary and secondary human ovarian follicles [76].…”
Section: Ovarian Cortex Transplantationmentioning
confidence: 99%
“…Los métodos de aislamiento folicular se dividen en tres categorías: enzimáticos [36][37][38] , mecánicos 18,39,40 , o una combinación de ambas [41][42][43][44][45] .…”
Section: Cultivo De Fp Aisladosunclassified
“…Aunque requiere más tiempo, este enfoque da como resultado una mejor conservación de la integridad y morfología folicular. Por otro lado, varios estudios [41][42][43][44][45] informaron resultados efectivos utilizando una combinación de ambos protocolos que incluían una breve digestión enzimática, seguida de un aislamiento por microdisección individual.…”
Section: Cultivo De Fp Aisladosunclassified
See 1 more Smart Citation